Detection of lard in a complex dehydrated stock - M. Balsells (Grasas y Aceites, 1993)
The detection of lard in food products is of special interest for reasons of quality, dietetics or religious belief. Works carried out to date have mainly concerned fatty mixtures with others food components. This work studies a complex food products (dehydrated stock model) containing hydrogenated palm and beef fat. An appraisal is carried out regarding the detection sensitivity to the addition of 0.2% lard, using data on sterols and fatty acids in the β position. This last model only appears reliable for the goal proposed.